The Impact of Mineral Resources on Development in Sub-Saharan Africa - HLAVOVÁ, Natália (Journal of Environmental Management and Tourism, 2017)
The aim of this paper is to identify the impact of natural resources on Human Development Index in the economies of sub-Saharan Africa. We begin with overview of some of the previous studies of natural resources and their impact on economic growth and other economic and non-economic indicators. Then we perform a regression analysis of the impact of the share of natural resources in total export on Human Development Index. The regression analysis showed that the higher share of natural resources in total export leads to the higher value of Human Development Index in the economies dependent on resource exports and has a negative effect in other economies.